Bactericidal efficacy of non-thermal plasma activation against Aeromonas hydrophila and immunological responses of koi (Cyprinus carpio haematopterus). Issue 121 (February 2022) - Kim, Sang Wha; Kim, Hyoun Joong; Kim, Sang Guen; Kwon, Jun; Lee, Sung Bin; Jung, Won Joon; Lee, Young Min; Jo, Su Jin; Giri, Sib Sankar; Yoon, Seok Hyun; Kim, Seon Ho; Kim, Chan Mo; et al.
Abstract: In the aquaculture industry, an efficient and safe water purification system is important to prevent mass mortality by virulent pathogens. As extensive use of traditional methods (e.g.: povidone-iodine, ozone, ultraviolet irradiation, formalin, and chlorine dioxide) have adverse effects on cultured fish, an appropriate and alternative water purification method is vital for the sustainability of the industry. Non-thermal plasma technology has been successfully used for various biomedical purposes (e.g: food sterilization, medical device disinfection, wound healing, cancer therapy, etc.) and has great potential to be used as a sterilizing system. However, few studies have been conducted on its usefulness in the aquaculture industry. In this study, we investigated the bactericidal efficacy of plasma-activated water induced by non-thermal plasma and its histopathological as well as immunological adverse effects on koi. A highly virulent Aeromonas hydrophila SNU HS7, which caused massive mortality of koi, was used for this study. Non-thermal plasma was applied for 10 min to the fish tanks with 1.2 × 10 9 CFU/mL SNU HS7 using PLMB-20 system to confirm the sterilization efficacy and to observe the survival and immunological reaction of koi for 14 days. As a result, gross pathological, histopathological, and immunological investigations did not reveal any significant adverse effects in fish as compared to the control groups. To the best of our knowledge, this is the first study showing that non-thermal plasma can be used for sterilization of rearing water without giving significant physiological damage to the fish, even under the assumption of extreme situations. As plasma can effectively sterilize not only bacteria but also other unknown pathogens, the results of this study are showing a promising future in purifying water in aquaculture practice. Highlights: Highly virulent A. hydrophila SNU HS7, toxic to koi, was isolated and identified. Non-thermal plasma treatment shows excellent bactericidal efficacy. First study to show–sterilization is possible without significant physiological damage to fish. Applying plasma to aquaculture can prevent diseases caused by unknown pathogens.